Innovative computational modeling of multiaxial fatigue analysis for notched components. (January 2016) - Ince, A.; Glinka, G.
Abstract: Most of the notched components for ground vehicles experience complex multiaxial loadings, where principal stresses rotate and change non-proportionally their magnitudes during a loading cycle. Furthermore, many vehicle components contain notches and geometrical irregularities because of design requirements. These geometric discontinuities cause significant stress concentrations. Multiaxial loads result in complex stress and strain responses at notch areas and can induce a fatigue failure even without any warning of noticeable plastic deformation. Unfortunately, the combination of multiaxial loading paths and complex geometries of mechanical components is unavoidable in practice and experiments performing durability test for ground vehicles are often not feasible because of time and cost considerations. Therefore, an innovative computational fatigue analysis methodology has been proposed here for multiaxial fatigue life analysis of notched components under design process using analytical and numerical methods. The proposed multiaxial fatigue analysis methodology consists of an elastic–plastic stress–strain model and a multiaxial fatigue damage parameter. Computed results of the proposed methodology are compared to sets of experimental published data to verify the prediction capability of the elastic–plastic stress–strain model and the fatigue damage parameter. A comparison of analysis results and experimental data shows that the multiaxial elastic–plastic stress–strain model correlates well with experimental strain data for SAE 1070 steel notched bars subjected to complex non-proportional load paths. The proposed fatigue damage parameter correlates well with fatigue data of 1045 steel and Inconel 718 tubular specimens under proportional and non-proportional loadings. Finally the complete analysis methodology incorporating both the elastic–plastic stress–strain model and the multiaxial fatigue damage parameter is found to be in a good agreement with experimental data of SAE 1045 steel notched shafts subjected to proportional and non-proportional loadings.